Effect Of Market Vegetable Waste Fermented Feeding On The Growth Of Red Cherry Ornamental Shrimp (Neocaridina davidi) - Wijaya, Rudy; Maulana, Muhammad Ihza; Setyawan, Agung Cahyo; Kusuma, Baruna (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
Red Cherry ornamental shrimp (Neocaridina davidi) is a freshwater ornamental shrimp that is in great demand for aquascape. Feed is one of the variables with the highest cost in the Red Chery ornamental shrimp farming business. This study was conducted to determine the effect of fermented feeding market vegetable waste on the growth of Red Cherry ornamental shrimp. This research was conducted in June-July 2021 using a Complete Random Racangan with 5 treatments and 3 tests at the Laboratory of the Faculty of Fisheries and Marine Sciences, Jenderal Soedirman University. The treatment given is the feeding of fermented feed from waste mustard, carrots, bean sprouts, and cabbage vegetables, as well as the feeding of spirulina as a control treatment. The observed parameters are absolute length and weight gain, specific growth rate, survival and water quality. The data from the study were analyzed statistically with the F ANOVA Test and the tukey test if there were differences between treatments. The results showed that the control treatment obtained markedly different results (P>0.05) from other treatments for absolute length and weight growth parameters. Bean sprouts vegetable waste gives the best yield (6.8±0.22%) for a specific growth rate. The survival rate value between treatments did not show any significantly different results (P<0.05). Water quality parameters in the maintenance medium are classified as feasible for the life of Red Chery ornamental shrimp. In this study, feed from fermented bean sprouts vegetable waste can provide the best growth for Red Chery ornamental shrimp